Report on a transborder spread of carbapenemase-producing bacteria by a patient injured during Euromaidan, Ukraine - Hrabák, J; Študentová, V; Adámková, V; Šemberová, L; Kabelíková, P; Hedlová, D; Čurdová, M; Zemlickova, H; Papagiannitsis, C C (New microbes and new infections, 2015)
Spread of carbapenemase-producing bacteria has been described all over the world. This phenomenon may be accelerated by many factors, including wars and natural disasters. In this report, we described an NDM-1-producing Klebsiella pneumonia ST11 recovered from a patient injured during the Maidan revolution in Ukraine. To our knowledge, this is the first report of a carbapenemase-producing Enterobacteriaceae in Ukraine and one of several reports describing wound colonization/infection of humans injured during war.
Keywords: war; ST11; NDM-1; Antibiotic resistance; Klebsiella pneumoniae; catastrophe; disaster